Pengaruh Inflasi, PDRB, Suku Bunga dan Tenaga Kerja Terhadap Nilai Tukar Petani Provinsi Lampung - Lidya Sari Mas Indah; Wan Abbas Zakaria; Dewi Mulia Sari (Department of Agricultural Social Economics, Faculty of Agriculture, Brawijaya University, 2023)
One indicator that shows the welfare of farmers is the Farmer's Exchange Rate (NTP). During the pandemic, farmers' purchasing power is still low. Analyze the effect of inflation, interest rates, labor, and GRDP on the Farmer's Exchange Rate in Lampung Province. This research was conducted by Lampung Province with the consideration that Lampung Province is one of the provinces with the largest production of agricultural sector products in Indonesia. The data used is secondary data (time series data) from 2010-2022. The analytical model used is the Autoregressive Ordinary Least Square (OLS) method. The results showed that inflation, labor, GRDP, and interest rates had a significant effect on Farmers' Exchange Rates in Lampung Province.Â Â